In utero hematopoietic cell transplantation: induction of donor specific immune tolerance and postnatal transplants - Peranteau, William H. (Frontiers in Pharmacology, 2014)
In utero hematopoietic cell transplantation (IUHCT) is a non-myeloablative non-immunosuppressive transplant approach that allows for donor cell engraftment across immunologic barriers. Successful engraftment is associated with donor-specific tolerance. IUHCT has the potential to treat a large number of congenital hematologic, immunologic, and genetic diseases either by achieving high enough engraftment levels following a single IUHCT or by inducing donor specific tolerance to allow for non-toxic same-donor postnatal transplants. This review evaluates donor specific tolerance induction achieved by IUHCT. Specifically it addresses the need to achieve threshold levels of donor cell engraftment following IUHCT to consistently obtain immunologic tolerance. The mechanisms of tolerance induction including partial deletion of donor reactive host T cells by direct and indirect antigen presentation and the role of regulatory T cells in maintaining tolerance are reviewed. Finally, this review highlights the promising clinical potential of in utero tolerance induction to provide a platform on which postnatal cellular and organ transplants can be performed without myeloablative or immunosuppressive conditioning.